The interaction between strike-slip dominated fault zones and thrust belt structures: Insights from 4D analogue models. (May 2019) - Fedorik, Jakub; Zwaan, Frank; Schreurs, Guido; Toscani, Giovanni; Bonini, Lorenzo; Seno, Silvio
Abstract: Strike-slip motion is a fundamental tectonic process around the globe often resulting in prominent surface expressions. The full reconstruction and comprehension of strike-slip dominated structures can be a major challenge due to the complexity of the associated fault patterns. Further complexities occur when strike-slip dominated structures in the foreland interact with thrust belt fronts. Starting from a well-studied natural example (the Sciacca Fault Zone in the Sicilian Channel, Italy) we ran a set of analogue models simulating the interaction between strike-slip dominated fault zones and thrust structures using quartz sand as the analogue material and X-Ray Computed Tomography as a technique to carry out a 4D analysis of model internal structures. During a first phase, a thrust belt was created in our models, which was subsequently affected by a perpendicular fault system that underwent either pure strike-slip, 10°-, 20°-, 30°-transtensional, or 10°-, 20°-, 30°-transpressional motion. In general, transpressional models form pop-up structures, while the pure strike-slip model develops one sub-vertical fault bounded by two converging reverse faults. The 10˚-transtensional model generates a set of Riedel shear faults, which merge during the later stages of deformation. This model also shows a positive elevation change along the strike-slip dominated structures near the intersection with the thrust belt. The 20˚-transtensional model contains some Riedel shear faulting as well, but is dominated by two normal faults with steep dip angles and some minor sub-vertical strike-slip faults in between. This fault architecture is also observed in our 30˚-transtensional model. Three different tectonic regimes interacting with pre-existing and newly formed thrust front led to very different structural settings. These results were of help in better defining the tectonic regime that controlled the strike-slip dominated part of the Sciacca Fault Zone, but they show a fair match with other natural examples as well. Highlights: Sandbox 4D analogue modelling. Strike-slip dominated structures and their interaction with a thrust belt. Splay faulting within the strike-slip deformation. Change of the structural styles due to an unequal stress conditions.